Concept of Life and Death in Iftekhar Arif’s Poetry - Iqbal, Amina M.; Sajid, Syed Aoun (sourcecoder, 2024)
The concept of Death and life are two inseparable realities. Death is actually the end of life. Everyone acknowledges the fact that every soul has to go through the harsh stage of death. Death is actually the name of the soul leaving and separating from the body. Death is not the name of annihilation, but the transition from one world to another world is called death. The concept of death and life has been a popular idea in the literature of the world. If we talk about Urdu literature, every known and unknown poet has written in it. Iftikhar Arif is considered one of the most distinguished poet of Urdu. His poetry has a prominent religious color. He has presented the concept of the status of the world and the hereafter in different ways in his poetry. On the concept of death and life there are many such poems in "Kitab-e- Dil-o- Duniya" which helps a lot to understand his opinion. The purpose of writing this research article is to clarify the concept of death and life in Iftikhar Arif’s poetry.